The Impact of Oil Shocks on Systemic Risk of the Commodity Markets - Dai, Zhifeng; Wu, Tong (Journal of systems science and complexity, 2024)
This study examines the influence of oil shocks on systemic risk spillover among the commodity markets. Specifically, this paper uses the DCC-GARCH approach combined with the TVP-VAR model to calculate risk connectedness and the GARCH-MIDAS model to explore how oil shocks from different sources affect the risk spillover effects among the commodity markets. The results are the following: First, there are significant risk spillovers among the commodity markets with important time-varying characteristics and with sharp changes in times of crisis. The industrial metals, agriculture, precious metals, and light energy commodity markets are risk recipients, and the energy and livestock commodity markets are risk exporters. Second, oil price shocks, particularly oil aggregate demand shocks, prominently affect the total risk connectedness among the commodity markets. In particular, the impact on the net risk spillover effect of different commodity market differs.